Delivering project SCORE in competitive youth sport settings - Ferreira, Marta; Santos, Fernando; Fernández-Villarino, María A.; Mergler, Jason; Strachan, Leisha; MacDonald, Dany J. (Frontiers in Sports and Active Living, 2024)
Introduction This study evaluates the effectiveness of the Project SCORE intervention in fostering Positive Youth Development (PYD) within competitive youth sport settings in Portugal. Project SCORE is an online PYD-focused tool developed to assist coaches in promoting the 4Cs—competence, confidence, connection, and character—within their coaching. Methods The research involved 13 coaches and 70 youth athletes from football and rowing teams. Methodologically, this study analyzed the pre- and post- Project SCORE intervention data, assessing the perceptions of coaches and athletes towards the development of the 4Cs. Results Results indicated significant improvements in athletes' perceptions of 4Cs post-intervention, and among coaches' perceptions, there was a significant improvement in the practice and transfer of life skills. Particularly, coaches showed enhanced abilities in fostering life skills and facilitating the transfer of these skills to competitive environments, although some dimensions like sport climate did not sustain positive changes. Discussion The findings highlight the benefits of customized PYD-based programs in competitive youth sports and suggest the need for further research to enhance their widespread and consistent implementation.